Theoretical and Numerical Study on a Scale Model Test of Planetary Cratering Impact - He Lv; Qiguang He; Xiaowei Chen (Aerospace)
Our investigation delves into the scaling law governing planetary cratering impacts. We meticulously analyze the interplay between dimensionless parameters driving crater growth and the morphological transition of craters and construct the scaling analysis between the scale model tests and the prototype tests by numerical simulation. With practical engineering applications in mind, we design scale model tests based on the experimental setups of geotechnical centrifuges, ensuring the robust validity of test designs. This meticulous approach is integral to achieving fidelity between simulations and experimental scenarios. Validation of our scale model tests is conducted through a numerical modeling framework, coupling the finite element-smoothed particle hydrodynamics adaptive method (FE-SPH). This validation procedure serves to bolster the reliability and credibility of our methodology, facilitating an accurate depiction of the cratering mechanism. Of particular interest is the investigation into the depth-to-diameter ratio of impact craters, wherein we explore its intricate relationship with projectile diameter and gravity. Through rigorous analysis, we delineate the transition diameter at which terrestrial impact craters manifest a transition from simple to complex morphologies, thereby shedding light on the underlying dynamics of crater formation. Moreover, our study meticulously scrutinizes the relationship of crater formation time between the scaling model tests and the prototype tests. Our research underscores the consistency of the crater depth–diameter ratio in the scale model tests and the prototype tests and affirms applicability in replicating prototype tests by scale model tests. Notably, our findings reveal compelling correlations between the depth-to-diameter ratio of impact craters and gravity, as well as projectile diameter, providing valuable insights into the governing dynamics of impact crater formation. These insights not only advance our fundamental understanding of planetary cratering processes but also hold implications for practical applications in planetary science and engineering.